Assistive Technology for Higher Education Students with Disabilities: A Qualitative Research - Konstantinos Papadopoulos; Eleni Koustriava; Lisander Isaraj; Elena Chronopoulou; Flavio Manganello; Rafael Molina-Carmona (Digital, 2024)
The objective of this qualitative investigation is to identify the assistive technology recognized by students with disabilities and to determine the assistive technology (software apps and devices) they require both at university and at home. A total of forty-two students, comprising 20 males and 22 females, were recruited from four different countries (Germany, Greece, Italy, and Spain) for participation in this study. The sample encompassed 10 students with visual impairments, 11 with hearing impairments, 11 with mobility impairments, and 10 with specific learning disabilities. Semi-structured interviews were conducted with the students either online or in person. Content analysis was employed to scrutinize the data obtained from these interviews. The outcomes of this analysis shed light on the assistive technology acknowledged, utilized, or desired by students with disabilities in both academic and domestic settings. The findings from this study carry practical implications for fostering inclusive and accessible education within higher education institutions, benefiting accessibility units/offices staff as well as teaching personnel.